Instrumentos de evaluación para los alumnos de segundo año de bachillerato de la especialidad de informática del Colegio De Bachillerato Dr. Camilo Gallegos Domínguez de la provincia Del Oro Del Cantón Arenillas período lectivo 2015 – 2016, lineamientos alternativos - Zapata Sanmartín, Viviana Anabel (2016)
This research paper entitled: “INSTRUMENTOS DE EVALUACIÓN PARA LOS ALUMNOS DE SEGUNDO AÑO DE BACHILLERATO DE LA ESPECIALIDAD DE INFORMÁTICA DEL COLEGIO DE BACHILLERATO DR. CAMILO GALLEGOS DOMÍNGUEZ DE LA PROVINCIA DEL ORO DEL CANTÓN ARENILLAS PERÍODO LECTIVO 2015 – 2016, LINEAMIENTOS ALTERNATIVOS”, alternative guidelines, carried out according to what stable Regulation of Academic System of the National University of Loja. The central problem of the research was: Are teachers using a properly assessment tools and what is the influence of assessment instruments? He was raised as a general objective: to analyze the use of assessment tools and their influence on the teaching-learning process of the sophomore year of college computer specialty Dr. Camilo Gallegos Dominguez. The methods used were: deductive, inductive, synthetic, statistical model, methodology used to collect the information necessary for the development of research, with the help of some techniques and research instruments such as direct observation activities the second high school class of the Education Unit under study, to verify the use of assessment tools in classroom activities and the survey of teachers and students for information to justify the investigation. The results revealed that during the educational process teachers use traditional techniques and tools for assessing skills and attitudes; since they do not use updated tools, and inadequate teaching little as oral and written, in addition to using slate and textbook and some, there is no equality of all teachers in the evaluation periods; the same that are geared solely to determine the knowledge acquired by students